Length-weight relationships of eighteen species of freshwater fishes from Panchet Reservoir in Ganges basin, Jharkhand, India - Sandhya, K.M.; Karnatak, Gunjan; ., Lianthuamluaia; Sarkar, Uttam Kumar; Kumari, Suman; Mishal, P.; Kumar, Vikash; Panda, Debabrata; Ali, Yousuf; Naskar, Bablu (Indian Journal of Fisheries, 2020)
The present study describes the length-weight relationships (LWRs) of 18 fish species from a large tropical reservoir, Panchet,Â  in the Damodar River basin, one of the main tributary of the largest river Ganga in India. A total of 2419 individuals represented by 18 species belonging to 9 families were sampled between November 2014 and June 2016. The b values ranged from 2.469 for Trichogaster chuna to 3.428 for Ailia coila. All the regressions were highly significant (p3, p